STRATEGI DAN IMPLEMENTASI DIGITAL MARKETING SELAMA PANDEMI COVID-19 - Ekadjaja, Margarita; Siswanto, Halim Putera (Jurnal Bakti Masyarakat Indonesia, 2021)
The Covid-19 Pandemic has been greatly affecting micro, small, and medium businesses, especially since the government issued the regulation on large-scale social distancing in order to reduce the spread of Corona virus. This community-engagement service activity aimed to socialize the digital marketing to market the products related to the Industrial Revolution 4.0 era and the existence of Covid-19 Pandemic. Limun Sari Buah is a type of medium-scale business established in 1970 producing lemonade drinks which are sold per crate consisting of 600 ml bottles. Currently, the sale of Limun Sari Buah is decreased due to the people’s activities reduction due to the pandemic and the lack of available flavor variants. The team of Community-Engagement Services attempts to provide a solution to Limun Sari Buah in the field of marketing according to the Industrial Revolution 4.0 era and diversifying the lemonade-drink product variants. The efforts done by the team of UNTAR Community-Engagement Services was by providing a training on marketing 4.0 entitled: The Strategy and Implementation of Digital Marketing in 4.0 Era through a webinar. The target of this community-engagement service activity for the business-owner and marketers is being able to market the products digitally by utilizing the internet media. After participating in the Marketing 4.0 Training, partners can use the internet media to market their products through Instagram. According to the result of a survey among 105 respondents in the age between 20-50 years old, the team of community-engagement services provide a solution to Limun Sari Buah to add new variants of the lemonade-drink product such as ginger-extract and milk-coffee. The output of this community-engagement service activity is disseminated in a National Seminar and Opini Untar. ABSTRAK: Pandemi Covid-19 berdampak besar pada usaha bisnis berskala mikro, kecil, dan menengah terutama sejak pemerintah mengeluarkan peraturan mengenai Pembatasan Sosial Berskala Besar dalam rangka mengurangi penyebaran virus Corona. Tujuan kegiatan abdimas ini adalah mensosialisasikan digital marketing untuk memasarkan produk sehubungan dengan era Revolusi Industri 4.0 dan terjadinya wabah pandemi Covid-19. Limun Sari Buah merupakan usaha bisnis berskala menengah, didirikan tahun 1970 dengan produk yang dihasilkan berupa limun dan dijual secara konvensional per krat dengan ukuran 600 ml per botol. Saat ini penjualan Limun Sari Buah berkurang karena berkurangnya aktivitas masyarakat keluar rumah akibat pandemi dan kurangnya varian rasa yang tersedia. Tim Abdimas berupaya memberikan solusi kepada Limun Sari Buah di bidang pemasaran sesuai era Revolusi Industri 4.0 dan di bidang diversifikasi varian produk minuman limun. Upaya yang dilakukan Tim Abdimas UNTAR adalah memberikan pelatihan pemasaran 4.0 dengan topik Strategi dan Implementasi Digital Marketing di Era 4.0 melalui webinar. Target kegiatan abdimas adalah pemilik dan tenaga pemasar mampu memasarkan produknya secara digital dengan pemanfaatan media internet. Setelah mengikuti pelatihan pemasaran 4.0, mitra dapat memanfaatkan media internet untuk memasarkan produknya melalui instagram. Berdasarkan hasil survei varian rasa tertinggi dari 105 responden yang berusia 20-50 tahun, Tim Abdimas memberikan solusi kepada Limun Sari Buah untuk menambah varian produk minuman limun, seperti sari jahe dan kopi susu. Luaran kegiatan abdimas ini dipublikasikan dalam Seminar Nasional dan Opini Untar.